Budaya Literasi Melalui Sastra Anak di Madrasah Ibtidaiyah Negeri Kabupaten Jember - Mislikhah, St.; Kristanti, Anjar Aprilia (Gurindam: Jurnal Bahasa dan Sastra, 2025)
The phenomenon of low literacy levels among Indonesian children urges formal educational institutions to develop an effective literacy culture. This study aims to describe (1) the planning,(2) implementation, and (3) evaluation carried out by Madrasah Ibtidaiyah Negeri Jember in uplifting a literacy culture through children’s literature. This research employed a qualitative approach and analyzed using Cresswell’s data analysis Spiral Technique. The findings indicate that (1) The planning phase of literacy culture development involves preparing school resources and infrastructure, (2) the implementation of literacy culture have different way each madrasag, reflecting the unique characteristics of the respective school, and (3) evaluation is conduct not only through formal testing, but also by facilitating enjoyable activities for students to engage with literacy practices.